The Starr report disrobed - Malti-Douglas, Fedwa (Columbia University Press, 2000)
""What is this strange book"" asks Fedwa Malti-Douglas, ""that can bring the American presidency to its knees?"" In this probing study of Kenneth W. Starr's influential and historic work, she reveals how The Starr Report exposed